Characterization of a human thyroid microtissue model for testing thyroid disrupting chemicals - E. Rogers; E. K. Breathwaite; T. Nguyen-Jones; S. M. Anderson; J. J. Odanga; D. T. Parks; K. K. Wolf; T. Stone; P. Balbuena; J. Chen; S. C. Presnell; J. R. Weaver; et al. (Frontiers in Toxicology, 2024)
Perturbation of thyroid hormone (T4) synthesis is known to cause numerous developmental, metabolic, and cognitive disorders in humans. Due to species differences in sensitivity to chemical exposures, there is a need for human-based in vitro approaches that recapitulate thyroid cellular architecture and T4 production when screening. To address these limitations, primary human thyrocytes, isolated from healthy adult donor tissues and cryopreserved at passage one (p’1) were characterized for cellular composition, 3D follicular architecture, and thyroglobulin (TG)/T4 expression and inhibition by prototype thyroid disrupting chemicals (TDC). Flow analysis of the post-thaw cell suspension showed >80% EpCAM-positive cells with 10%–50% CD90-positive cells. When seeded onto 96-well Matrigel®-coated plates and treated with bovine thyroid stimulating hormone (TSH), thyrocytes formed 3D microtissues during the initial 4–5 days of culture. The microtissues exhibited a stable morphology and size over a 14-day culture period. TG and T4 production were highest in microtissues when the proportion of CD90-positive cells, seeding density and thyroid stimulating hormone concentrations were between 10%–30%, 6K–12K cells per well, and 0.03–1 mIU/mL, respectively. At maximal TG and T4 production levels, average microtissue diameters ranged between 50 and 200 µm. The T4 IC50 values for two prototype TPO inhibitors, 6-propyl-2-thiouracil and methimazole, were ∼0.7 µM and ∼0.5 µM, respectively, in microtissue cultures treated between days 9 and 14. Overall, p’1 cryopreserved primary human thyrocytes in 3D microtissue culture represent a promising new model system to prioritize potential TDC acting directly on the thyroid as part of a weight-of-evidence hazard characterization.